Synthesis of new elementsubstituted derivatives of 3H-pyrrolizines - Kissounko, Denis A; S. Kissounko, Natal'ya; Krut'ko, Dmitry P; Brusova, Galina P; Lemenovskii, Dmitry A; Boag, Neil M (Journal of organometallic chemistry, 1998)
The anion of 3H-pyrrolizine was isolated as its lithium 2a and thallium salts 3 and the anion of 1-methyl-3H-pyrrolizine as its lithium salt 2b. Reaction of the lithium anions with Group 14 electrophiles led to a number of substituted derivatives of the 3H-pyrrolizine ring system. In the case of 2b it was shown that the number of isomers obtained was strongly dependent on the reaction solvent.